Implementing a national flexible sigmoidoscopy screening program: results of the English early pilot - Bevan, Roisin; Rubin, Greg; Sofianopoulou, Eleni; Patnick, Julietta; Rees, Colin J. (Endoscopy, 2015)
Background and study aims: Following the results of a major UK study showing that once-only flexible sigmoidoscopy (FSIG) screening significantly reduced colorectal cancer (CRC) incidence and mortality, an FSIG screening program in England was announced in late 2010. Three “early pilot” sites were selected in 2011 in Derby, South of Tyne, and Tees to assess the practicalities of the delivery of FSIG screening.Participants and methods: Eligible people aged 55 from selected practices in the three early pilot areas received postal invitations to participate. The South of Tyne and Derby sites employed interactive models of screening invitation, while Tees used a simple invitation. Data were collected to assess uptake, process, and outcome. A self-completion participant satisfaction questionnaire was sent to all participants 1 month after attendance. Results: A total of 4023 55-year-olds were invited to participate. Uptake was 29 %, with 1151 people screened over a 3-month period. Screening uptake differed by method of invitation: a simple approach was significantly more successful than an interactive one (32 % vs. 27 %, P = 0.0015). Uptake decreased significantly with increasing deprivation. Adenomas were found in 111 (9.8 %) of those screened and cancer in two. The procedure was rated “very” or “fairly” acceptable by 97 % of participants. Over 90 % of respondents said they would participate in future cancer screening and a similar proportion would recommend doing so to others. Conclusion: Delivery of an FSIG screening program to prevent CRC is feasible and should be implemented using a simple invitation system. The national Bowel Scope program subsequently commenced at pilot sites in May 2013, with full implementation planned by 2016.